Correlation between body composition and bone mineral density in obese pre-menopausal women - Ningrum, Farah Hendara; Riwanto, Ignatius; Sukmaningtyas, Hermina; Adi, Kusworo; Pemayun, Tjokorda Gde Dalem; Santoso, Antonius Gunawan; Kuntjoro, Rr. Lydia Purna Widyastuti Setjadiningrat; Jannah, Miftahul; Hendrianingtyas, Meita (Edelweiss Applied Science and Technology, 2024)
Obese condition which causes changes in body composition affect to very serious consequences on Bone Mineral Density (BMD). This study aims to analyze correlation between body composition that consist of lean mass, fat mass, and visceral fat rating with Bone Mineral Density. Cross-sectional study that conducted from June-December 2023 at Diponegoro National Hospital (RSND) Semarang. Body composition respondent was measured using Tanita Body Analyzer and bone mineral density respondent was analyzed using Dual X-ray absorptiometry (DXA) in Semarang Medical Center. Statistical Analysis for correlation in this study using Spearman Test. Total 100 respondent in this study was in obese condition with mean body mass index 33.08 ± 5.42 kg/m2. There was no significant correlation between lean mass and total fat mass with bone mineral density (p>0.05) but, viseral fat rating and bone mineral density having significant correlation with p=0.021 with weak correlation strength r=0.230. Positive correlation was found among body composition that consist of fat mass, lean mass, and visceral fat rating with bone mineral density but, significant correlation only found in visceral fat fat rating and bone mineral density (p=0.021).